2004
DOI: 10.1017/s0952836904004996
|View full text |Cite
|
Sign up to set email alerts
|

Is the highveld mole‐rat Cryptomys hottentotus pretoriae (Rodentia: Bathyergidae) an induced or spontaneous ovulator?

Abstract: The highveld mole-rat Cryptomys hottentotus pretoriae is a social subterranean rodent that exhibits seasonal reproduction. Non-reproductive females remain anovulatory whilst in the confines of the natal colony. However, during the southern hemisphere summer, dispersal of non-reproductive females from the natal colony occurs with subsequent pairing with unrelated males. This study investigates whether the dispersing female highveld mole-rat is an induced or spontaneous ovulator. Eight non-reproductive females w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…The two sexes from this species meet very briefly for procreation. It has been speculated upon that the common mole-rat, Cryptomys hottentotus hottentotus [31] may be an induced ovulator, while studies on the highveld mole-rat, C. hottentotus pretoriae and the Natal mole-rat, C. hottentotus natalensis, have revealed that females tend to undergo induced ovulation [6] and [7]. In marked contrast, the naked mole-rat is a spontaneous ovulator [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two sexes from this species meet very briefly for procreation. It has been speculated upon that the common mole-rat, Cryptomys hottentotus hottentotus [31] may be an induced ovulator, while studies on the highveld mole-rat, C. hottentotus pretoriae and the Natal mole-rat, C. hottentotus natalensis, have revealed that females tend to undergo induced ovulation [6] and [7]. In marked contrast, the naked mole-rat is a spontaneous ovulator [8].…”
Section: Discussionmentioning
confidence: 99%
“…In social, seasonally breeding bathyergids occurring in environments where rainfall is predictable, dispersing females of the highveld mole-rat, Cryptomys hottentotus pretoriae [6] and Natal mole-rat, Cryptomys hottentotus natalensis [7] also exhibit induced ovulation. This is in marked contrast to the eusocial naked mole-rat, Heterocephalus glaberwhich occurs in ecologically constrained environments where rainfall often fails or is sporadic and spontaneous ovulation is the modus operandi [8].…”
mentioning
confidence: 99%
“…Thus, strong selective pressure for both seasonal reproduction and induced ovulation, where mating triggers ovulation, reducing the latency from pairing to conception, has led to the evolution of these traits in solitary species of mole-rats inhabiting regions with a predictable and seasonal rainfall (Georychus and Bathyergus) [38,40,68 -70]. This is mirrored in Cryptomys, where induced ovulation occurs in the cooperatively breeding highveld mole-rat, Cryptomys hottentotus pretoriae, and the Natal mole-rat, Cryptomys hottentotus natalensis [71,72]. A common characteristic of these species, apart from the Natal mole-rat, is that they are all either seasonally breeding and or dependable on regular and predictable but short lived mating opportunities.…”
Section: (C) Reproduction and Reproductive Suppressionmentioning
confidence: 99%
“…Indeed, in the tuco tucos, the presence of spines may also facilitate lock during mating and the removal of copulatory plugs, thus facilitating sperm competition (Ramm, Parker and Stockley 2005). Induced ovulation has been found in both solitary and cooperatively breeding species (van Sandwyk and Bennett, 2005, Malherbe et al 2004and Jackson and Bennett, 2005. A characterstic feature of these taxa is that they are either seasonally breeding or ar depemdent on short lived mating encounters.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in progesterone concentration between the extracted and nonextracted pools and as a consequence we used the neat urine to measure native progesterone. The use of non-extracted urine to investigate patterns of ovulation has been succesfully used in other roednet moles (Malherbe et al 2004;Jackson and Bennett 2005;van Sandwyk and Bennett 2005;Snyman et al 2006;Faulkes et al 2010). We spiked the standard curve with 6 samples at a dilution of 1:16 from a pool of urine of low concentration to these 50μL of progesterone in increasing concentrations (0.3, 1.6, 6.4, 31.8, 63.6 and 127.2 nmols/l) whucg were subsequently assayed in dupicate.…”
Section: Radioimmunoassaymentioning
confidence: 99%